Characterising winery wastewater composition to optimise treatment and reuse. (8th September 2020) - Johnson, M.B.; Mehrvar, M.
Abstract: Background and Aims: Optimising the treatment and reuse of winery wastewater (WWW) can have positive environmental significance. Estimating the concentration of various organic compounds, nutrients, and metals via correlations with easily determined parameters could provide a rapid and cost‐effective method of characterising WWW and allow real‐time process adjustments to optimise the process performance. Methods and Results: A total of 367 samples of WWW collected in the Niagara Region, Ontario, Canada, were analysed for pH, electrical conductivity, solids fractions, oxidisable materials, nutrients and metals. The data were subjected to least and median squares regression. Conclusions: Robust correlations were developed between pH, electrical conductivity, total solids, total volatile solids and total suspended solids; and key measures of organic and nutrient loadings to wastewater treatment trains, including chemical oxygen demand, 5‐day biochemical oxygen demand, total Kjeldahl nitrogen and total phosphorus. The ability to predict metal concentration was more limited. Least median squares regression was used to identify potential outliers and to improve the fit of the equations (adjusted R 2 as high as 0.95). Significance of the Study: The correlations provide a promising, rapid and cost‐effective means of characterising WWW in the Niagara Region. This approach could also be used to develop relationships specific to other winemaking regions.